Comunicação midiática e educação na cibercultura - Magnoni, Antonio Francisco [UNESP]; Silva, Daniele Fernandes da [UNESP] (Pontificia Universidade Catolica do Parana - PUCPR, 2012)
This article aims to discuss how communication can contribute effectively with education in cyberculture, by design of educational environments that are configured according to the specific language of cyberspace. We consider digital technologies as language and therefore as forms of communication. As a theoretical basis, we use Peircean semiotics, for questions relating to language; the concept of technologies of intelligence, to the relation of the technique with digital media and the concepts of emergency and of transmiting architecture to think of cyberspace communication interfaces. We made a brief reflection on the political, administrative, social, cultural and economic problems that hinder the development of more appropriate forms of education for cyberculture. Then we point out some similarities between the fields of education and communication and made some observations about qualities of digital media that can contribute to a mbetter use of it as an educational tool. Finally, we indicate an educational and communicational gaming approach as a possible way to make communication technologies interactive audiovisual interfaces, able to educate in the age of cyberculture.

Este artigo tem por objetivo discutir como a comunicação pode contribuir de forma efetiva com a educação na cibercultura, por meio do projeto de ambientes educativos que se configurem conforme a linguagem específica do ciberespaço. Consideramos as tecnologias digitais como linguagem e, portanto, como formas de comunicação. Como base teórica, utilizamos a semiótica peirceana, para as questões referentes à linguagem, o conceito de tecnologias da inteligência, para a relação da técnica com mídias digitais e os conceitos de emergência e de arquitetura transmissível para pensar as interfaces comunicacionais do ciberespaço. Fizemos uma breve reflexão sobre os entraves políticos, administrativos, sociais, culturais e econômicos que impedem o desenvolvimento de formas de educação mais apropriadas à cibercultura. Depois, apontamos algumas aproximações entre os campos da educação e da comunicação e fizemos algumas observações sobre qualidades das mídias digitais que podem contribuir para o melhor aproveitamento delas como ferramenta educacional. Finalmente, indicamos uma abordagem educativo-comunicacional dos games como uma possível saída para fazer das tecnologias comunicacionais interfaces audiovisuais interativas, capazes de educar na era da cibercultura.
Mediatic communication and education in cyberculture
Keywords: Mediatic communication; Cyberculture; Education; Games; Comunicação midiática; Cibercultura; Educação; Games